Proposing work-environment inhibitors to informal work-place learning amongst Malaysian accountants - Abdul Wahab, Muhammad Syahir; Selamat, Mohamad Hisyam (World Business Institute, 2011)
This paper proposes twelve propositions on the work environment inhibitors to informal work-place learning activities amongst accountants in public accounting firms. The inhibitors are lack of time due to heavy work-loads, far away from colleagues’ working areas, absence of experts, lack of meaningful rewards for learning, lack of funds for learning and lack of proximity to learning materials. Other inhibitors include lack of access to computer technology, limited power in organizational affairs, reluctance of others to support learners, working policies discourage learning, structural inhibitors and mistakes are not tolerated during learning or early application of new ideas and skills. From the discussion, it is suggested that the firms and professional accounting bodies should have robust strategies to overcome those inhibitors. This is important to create a conducive environment for informal work-place learning activities and, in turn, increases accounting professionalism.